2024
DOI: 10.3389/fnut.2023.1281879
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamins A, C, D, E in cancer prevention and therapy: therapeutic potentials and mechanisms of action

Wamidh H. Talib,
Dima Abdulraheem Ahmed Jum’AH,
Zeena Shamil Attallah
et al.

Abstract: Cancer, a leading global cause of mortality, arises from intricate interactions between genetic and environmental factors, fueling uncontrolled cell growth. Amidst existing treatment limitations, vitamins have emerged as promising candidates for cancer prevention and treatment. This review focuses on Vitamins A, C, E, and D because of their protective activity against various types of cancer. They are essential as human metabolic coenzymes. Through a critical exploration of preclinical and clinical studies via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 144 publications
0
2
0
Order By: Relevance
“…Furthermore, numerous discoveries have highlighted numerous biological properties, outside of bone metabolism, including inhibiting tumor cell growth, angiogenesis, and cell metastasis and inducing apoptosis in various tumor types [ 69 ]. Numerous studies have shown that lower serum 25(OH)D levels are linked to a higher risk of developing various types of tumors, while high 25(OH)D levels have been found to have a protective effect against the development of cancer [ 70 , 71 ]. Furthermore, taking a vitamin D supplement in patients diagnosed with cancer has been linked to a favorable prognosis [ 72 , 73 , 74 ].…”
Section: Healthy Lifestyle and Cancermentioning
confidence: 99%
“…Furthermore, numerous discoveries have highlighted numerous biological properties, outside of bone metabolism, including inhibiting tumor cell growth, angiogenesis, and cell metastasis and inducing apoptosis in various tumor types [ 69 ]. Numerous studies have shown that lower serum 25(OH)D levels are linked to a higher risk of developing various types of tumors, while high 25(OH)D levels have been found to have a protective effect against the development of cancer [ 70 , 71 ]. Furthermore, taking a vitamin D supplement in patients diagnosed with cancer has been linked to a favorable prognosis [ 72 , 73 , 74 ].…”
Section: Healthy Lifestyle and Cancermentioning
confidence: 99%
“…Tumor cells undergo a metabolic shift from oxidative phosphorylation to glycolysis to meet their energy demands. Consequently, an excess of VC may impede glucose transport and adenosine triphosphate (ATP) production, triggering an energy crisis and eventual cell death (Figure 3) [65]. Furthermore, GLUT1 expression indirectly influences the effectiveness of tumor treatment.…”
Section: Vc Enhances the Efficacy Of Starvation Therapymentioning
confidence: 99%